2007
DOI: 10.1103/physrevlett.99.213004
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Inversion between Main and Satellite Lines in Atomic Photoionization

Abstract: The 1s photoionization of atomic Li was studied by photoelectron spectroscopy in the photon energy region between 85 and 140 eV for the ground state and the three lowest excited configurations Li(*) 1s(2)nl, nl=2p, 3s, 3p. The importance of electron correlations was investigated by comparing the multielectron transitions, so-called shake-up and conjugate shake-up satellites, and the direct process, so-called main lines. The relative intensity of the satellites increases with the level of initial excitation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Furthermore, the cross section for IE increases from 23% of the pure 1s-ionization cross section for Lið2sÞ to 70% for Lið2pÞ. Cubaynes et al [13] observed this behavior even more pronounced for higher excited initial nl levels. Since the initial-state alignment of their target was not determined, no conclusive result on the alignment dependence was obtained.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, the cross section for IE increases from 23% of the pure 1s-ionization cross section for Lið2sÞ to 70% for Lið2pÞ. Cubaynes et al [13] observed this behavior even more pronounced for higher excited initial nl levels. Since the initial-state alignment of their target was not determined, no conclusive result on the alignment dependence was obtained.…”
mentioning
confidence: 75%
“…On one hand this is expected for the shakeup transitions 2p ! np (n > 2) which constitute roughly 80% of the IE intensity [13]. On the other hand this indicates that also the conjugate shakeup transitions 2p !…”
mentioning
confidence: 99%
“…In Lithium [34] the shake-up probabilities have been examined in a systematic way by following higher excitations and their energy dependence. The increased shake-up probability in the core ionization of excited states has been attributed to an improved overlap between the initial state and final state wave-functions [34].…”
Section: Laser-excited Atoms 4d Photoelectron Spectramentioning
confidence: 99%
“…In a recent study on atomic Li laser-excited to the Li*1s 2 3p 2 P 3/2 state, it was shown that the satellites become even stronger than the main line [46]. In Fig.…”
Section: Article In Pressmentioning
confidence: 97%
“…9. Relative intensities with respect to the 1s main photoline (ML) for the shake-up (a) and the conjugate shake-up (b) satellites for ionization from the Li*1s 2 2p, 3s and 3p excited states (from [46]). Fig.…”
Section: Article In Pressmentioning
confidence: 99%